2013
DOI: 10.1212/wnl.0b013e31828f1876
|View full text |Cite
|
Sign up to set email alerts
|

Topography of dilated perivascular spaces in subjects from a memory clinic cohort

Abstract: Objective: To investigate whether the topography of dilated perivascular spaces (DPVS) corresponds with markers of particular small-vessel diseases such as cerebral amyloid angiopathy and hypertensive vasculopathy.Methods: Patients were recruited from an ongoing single-center prospective longitudinal cohort study of patients evaluated in a memory clinic. All patients underwent structural, high-resolution MRI, and had a clinical assessment performed within 1 year of scan. DPVS were rated in basal ganglia (BG-DP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
155
4
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(176 citation statements)
references
References 29 publications
16
155
4
1
Order By: Relevance
“…5,6 In a retrospective multicentre cohort study of 121 patients with ICH, patients with lobar ICH had a higher prevalence of severely dilated PVS in the centrum semiovale compared with patients with nonlobar ICH. 5 Further evidence for a link between CAA and dilated PVS was provided by a study on 89 memory clinic subjects, in which subjects with a high degree of dilated white matter PVS had higher counts of lobar microbleeds, a potential marker of CAA pathology.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 In a retrospective multicentre cohort study of 121 patients with ICH, patients with lobar ICH had a higher prevalence of severely dilated PVS in the centrum semiovale compared with patients with nonlobar ICH. 5 Further evidence for a link between CAA and dilated PVS was provided by a study on 89 memory clinic subjects, in which subjects with a high degree of dilated white matter PVS had higher counts of lobar microbleeds, a potential marker of CAA pathology.…”
Section: Discussionmentioning
confidence: 99%
“…The association of AD and increased white matter PVS volume has also been demonstrated using neuroimaging (Ramirez et al, 2015). PVS in the centrum semiovale (CSO-PVS) are associated with CAA-related intracerebral haemorrhage (ICH) (Charidimou et al, 2013b;Charidimou et al, 2014b) and its "haemorrhagic" markers, namely lobar microbleeds (Martinez- Ramirez et al, 2013;Yakushiji et al, 2014) and cortical superficial siderosis (Charidimou et al, 2014a). Indeed, a recent study using post-mortem 7-Tesla MR in CAA-related ICH found an association between juxta-cortical PVS enlargement and the histopathological grade of CAA in the overlying cortex (van Veluw et al, 2015).…”
Section: Mri-visible Perivascular Spaces (Pvs) -Sometimes Termed Vircmentioning
confidence: 96%
“…Whereas enlargement in the basal ganglia (BG-PVS) appears to be associated with markers of arteriolosclerosis, enlargement of PVS in the white matter centrum semi-ovale (CSO-PVS) appears to be associated with cerebral Aβ pathologies, both AD and CAA (Charidimou et al, 2013a;Charidimou et al, 2013b;Martinez-Ramirez et al, 2013). Neuropathological studies have demonstrated that the frequency and severity of white matter PVS is greater in AD than controls, and this was associated with brain Aβ load, severity of CAA and Apolipoprotein E (APOE) ε4 presence (Roher et al, 2003).…”
Section: Mri-visible Perivascular Spaces (Pvs) -Sometimes Termed Vircmentioning
confidence: 99%
“…69,72 Patients with SVD often have enlargement of the Virchow-Robin perivascular spaces, 73,74 which are associated with amyloid angiopathy, hypertension, and lobar microbleeds. 75,76 At this time, the clinical significance of the dilatation of the perivascular spaces remains to be determined.…”
Section: Pathophysiology Of White-matter Injury In Small Vessel Diseasementioning
confidence: 99%